An experience of application of the module-rating system in course of the physics for engineers - Куліш, В. В.; Кулішенко, В. М.; Кузнєцова, О. Я.; Пастушенко, С. М. (Proceedings of National Aviation University (archive), 2003)
Organization foundations and methodical peculiarities of a new version of the module-rating system are presented in the article. The forming the semester plan-schedule of the training process, preparation of the working journal with accordance to a special elaborated form, and preparation of the materials for written current control for each study are key points of the proposed system.Methods of conducting the studies accordingly to the system proposed are determined by presence of the following. The first is writing form of semester examinations, and the second is connected with the increasing the role of self-reliant student work that is typical for the last trends of the Ministry of Education and Science. The system main idea is the modeling typical examination situation during every practical study. In time, the practical study consists of the two characteristic parts. This includes the control of theoretical training (in the form of a short written control work) and the oral defense of the home tasks. By this way the required conditions for rhythmical student work during semester are arranged.Experience of application of the proposed new version of the module-rating system showed its high efficiency